Status of Para-teachers in India - Eswaran, S.; Singh, Ajit (JOURNAL OF INDIAN EDUCATION, 2009)
Over the last a few years, para-teachers are being recruited in almost all the states in India. This is primarily being done to meet the shortage of teachers particularly in primary and upper primary schools. At present there are more than half a million para-teachers. The present study covered 22 states which are affiliated to the All India Primary Teachers’ Federation. Of these states, only 6 states are not recruiting para-teachers and the rest are recruiting them. Parateachers are being deployed both in rural and urban areas. Only in some states such as Chhattisgarh, Haryana, Rajasthan and West Bengal, they are being deployed in rural areas only. The nomenclature of para-teachers is different in different states. Para-teachers are being appointed against vacant posts of teachers and additional posts created under Sarva Shiksha Abhiyan. Professional qualification for appointing para-teachers is not mandatory in states like Andhra Pradesh, Bihar, Chhattisgarh, Jharkhand, Meghalaya, Uttar Pradesh, Uttarakhand and West Bengal. So in these states, professionally untrained teachers are being appointed as para-teachers. Some states such as Gujarat, Haryana, Madhya Pradesh, Maharashtra, Orissa and West Bengal have discontinued appointment of regular primary teachers. In these states only para-teachers are being appointed. Local authorities such as Village Education Committee, Zila Panchayat/PRI have also been empowered to make recruitment of para-teachers. Remuneration being paid to para-teachers is much less than that which is paid to regular teachers. State governments are exploiting these teachers. The tenure of appointment of para-teachers ranges from one to five years. But most of the states are appointing para-teachers for one year or so. Only few states such as Gujarat, Orissa, Maharashtra and Himachal Pradesh have made some provisions for regularising the services of para-teachers.